Studi Eksplorasi Kesiapan Adopsi Manajemen Data Penelitian (Research Data Management) Perpustakaan Perguruan Tinggi di Indonesia - Atin Istiarni; Irhamni Ali (Media Pustakawan, 2022)
After digital repository, several governments have prioritized Research Data Management (RDM). Indonesia lacks RDM research. This study explores the most important technological, organization, and environment elements for RDM adoption. This project employs qualitative data via document analysis, interviews, and surveys based on qualitative data analysis. Quantitative data analysis will use Exploratory Factor Analysis (EFA) to find variable-influencing components. The study found that government policies and leadership are the biggest barriers to RDM adoption in Indonesian academic libraries. Technology is ready. Despite this, RDM and repository are still equated. Organizational aspects have also been considered, however in certain tertiary institutions, libraries and university research institutes share data management responsibility. This research will begin MDP adoption discussions in Indonesian university libraries.